Crop residue management and oxalate‐extractable iron and aluminium explain long‐term soil organic carbon sequestration and dynamics. (May 2016) - Van De Vreken, P.; Gobin, A.; Baken, S.; Van Holm, L.; Verhasselt, A.; Smolders, E.; Merckx, R.
Abstract : The management of crop residues affects carbon (C)‐sequestration. This study aimed to identify the interaction between residue management and soil properties on C‐sequestration. The hypothesis was that larger silt and clay contents and larger residue inputs enhance C‐sequestration. The soil was sampled in Belgium in long‐term (≥ 15 years) cropping systems with grain maize, Zea mays L. (all stover (leaves and stalks) returned), silage maize (all stover removed) or permanent grass. The fields sampled were distributed over two adjacent regions; one with sandy soil (33% silt + clay) and one with silty loam soil (71% silt + clay). The 13 C abundance of the soil organic carbon (SOC) revealed that topsoil (0–30 cm) under grain maize contained more maize‐derived SOC than that under silage maize (14 ± 1 and 9 ± 1 Mg C ha −1, respectively, P < 0.001, in sand, and 17 ± 1 and 14 ± 1 Mg C ha −1, respectively, P < 0.001, in silty loam). Total SOC stocks were unaffected by crop management, however, which suggests substitution of native SOC by fresh SOC derived from residues, especially in sandy soil where the silt and clay fraction is saturated with SOC. The maize‐derived SOC stocks of the silty loam soil are 3.5–5.5 Mg C ha −1 larger than those of the sandy soil, which confirms the larger potential of the former to sequester C. Surprisingly, the native C3 ‐SOC stocks in the sandy soil were 25–30 Mg C ha −1 larger than those of the silty loam soil. The concentration of SOC in the silt and clay fraction was on average three times larger for the sandy than for the silty loam soil. The concentration of oxalate‐extractable Al and Fe in the same fraction was on average 2.5 times larger for sandy than for silty loam soil. Silt and clay‐associated SOC correlated with the Fe + Al concentration across all regions and treatments ( R 2 = 0.62). This suggests that organo‐mineral associations and the formation of organo‐metal complexes promote C‐sequestration in this temperate region. Highlights: Different factors affect carbon stocks under two contrasting soils and four cropping systems. Returning maize residues promotes substitution of native soil organic carbon by maize‐derived carbon. Organo‐mineral interactions in the silt and clay fraction enhance carbon sequestration. The legacy of historical plaggen manuring has a strong effect on native soil carbon stocks.